Additions to the morphology of the Phyllophoridae and the Sclerodactylidae. I. Type species of Phyllophorella, Selenkiella, Cladolella and Clarkiella, with the description a new species of Thorsonia (Holothuroidea: Dendrochirotida) - Martins, Luciana; Tavares, Marcos (Zootaxa, 2022)
The phyllophorids Phyllophorella robusta, Selenkiella siamense and Cladolella virgo, as well as the sclerodactylid Clarkiella discoveryi, are the type species of their respective genera, all described by Heding & Panning (1954) and each known only from a single specimen, were revisited in order to reassess their morphology by means of optical and electron microscopy, and micro-computed tomography. Additionally, a new species of phyllophorid is described, the fourth of the genus Thorsonia.